The Role of Trust in Increasing Participation in Digital Cash Waqf in Wonogiri Regency - Dhiyaul Aulia Zulni; Nala Syifa Dewanti; Hanif Nur Rokhim (Institut Agama Islam Sunan Giri Ponorogo, 2025)
Digital cash waqf has great potential in optimizing Muslims' contribution to social and economic development. However, participation in digital cash waqf in Indonesia, particularly in Wonogiri Regency, remains low. This study aims to identify factors influencing individuals' intention to participate in digital cash waqf, focusing on the role of trust as a mediator between waqf literacy, social media, perceived usefulness, and perceived ease of use. The research method used is a quantitative approach with primary data collection through questionnaires distributed to 226 respondents in Wonogiri Regency. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that perceived usefulness, ease of use, and trust significantly influence participation intention in digital cash waqf. Although waqf literacy and social media influence did not show significant direct effects, both played a role through the mediation of trust. Trust fully mediated the relationship between waqf literacy and participation intention, as well as between social media and participation intention. Meanwhile, perceived ease of use had both a direct effect and a partial mediation effect on participation intention. Based on these findings, it is recommended that waqf management institutions improve transparency and user trust, and optimize the ease of use of digital platforms to encourage greater participation in digital cash waqf